Efeito das atividades antrópicas na bacia do Ribeirão Vermelho (Lavras, MG) sobre o ecossistema aquático - Menezes, João Paulo Cunha de (2016)
The worldwide trend toward conversion of agricultural and urbanized forest areas affects the aquatic environment in many ways; increasing pollution, decreasing biodiversity and degrading ecosystems making them no longer able to provide ecosystem services to humans and other species. Researchers and managers are becoming increasingly aware of the negative trends of urban development; and the effects in the changes of land use on aquatic ecosystems require monitoring. Thus, this paper investigates an integrated way the effects of land use and urban development in a highly impacted aquatic ecosystem. To such it were used physical-chemical properties of water and biological indicators and, complementarily was developed thematic maps of land use within the studied watershed. By multivariate statistical techniques was possible to determine the impact caused by the different land uses and to identify the best biological indicators for monitoring the lotic system. It was found an impact gradient comprising the sites classified as natural and affected. There was also a strong relationship of land use on water quality, having urban areas as the main source of contamination, because of the disposal of organic matter in the water body. However, the high organic loads combined with the low flow of the main water course (Ribeirão Vermelho) were not sufficient for its self-purification. Using the Street-Phelps model, it was found that the Ribeirão Vermelho waters are outside the limit range recommended by the resolution of the Ministry of Environment as to the concentrations of organic matter. The assessment of structure, benthic communities and its functional attributes was used to evaluate the indicators association with the places that describe the quality gradient. The best selected indicators are associated with higher levels of human disturbance; this may be due to the limited data set and the compact gradient of study. Due to the nature of the indicators, it is necessary to include the data of preserved areas in order to increase the quality gradient. Given the above, it is suggested the implementation of an integrated approach to assess the health of urban aquatic ecosystems involving the analysis of processes at an ecosystem level as well as structural and functional biological indicators.